2018
DOI: 10.1177/0305735618812199
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the reminiscence bump of very long-term memory for popular songs in old age: A non-linear mixed model approach

Abstract: Recognition of popular songs from one’s past shows a phenomenon that is known as a “reminiscence bump” from autobiographical memory research, namely, the increased recognition performance of songs from one’s youth and early adulthood. As a first goal of the present study, a non-linear functional relation between popular song recognition performance and song-specific age of an individual was examined. As a second goal, individual differences in recognition performance curves were taken into account by including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, the magnitude of the random factor “song” can be estimated from previous research: As revealed by Zimprich and Wolf (2016), every recognized song in their study which fell under the category of “bump years” (the age range between 10 and 30 years) decreased the mean of the memory distribution by 1.77 years. In contrast, Zimprich (2020) reported that the number of recognized songs resulted in a higher and later bump. These random effects cannot be avoided as long as no standardized set of musical stimuli and no research design is used; however, we point out that our multilevel regression analysis (see Column 1 of Table S7 in the Supplemental Material section) only revealed a relatively small contribution of 8.9% for this random part of the total variance.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the magnitude of the random factor “song” can be estimated from previous research: As revealed by Zimprich and Wolf (2016), every recognized song in their study which fell under the category of “bump years” (the age range between 10 and 30 years) decreased the mean of the memory distribution by 1.77 years. In contrast, Zimprich (2020) reported that the number of recognized songs resulted in a higher and later bump. These random effects cannot be avoided as long as no standardized set of musical stimuli and no research design is used; however, we point out that our multilevel regression analysis (see Column 1 of Table S7 in the Supplemental Material section) only revealed a relatively small contribution of 8.9% for this random part of the total variance.…”
Section: Discussionmentioning
confidence: 89%
“…The study by Loveday et al (2020) joins this line of research on the role of personally relevant music during the developmental phase of adolescence and early adulthood (10–30 years): Based on self-selected songs suggested by guests of a long-running radio show, it was found that 50% of selected songs had a personal significance (links to memories of a person) released during the ages of 10 to 30 with a peak between 10 to 20 years. The influence of individual variables such as sex or musical preference for genres on the location of the age peak for song preference was observed by Zimprich (2020): In a sample of persons aged 70–75 years, a maximum point (memory bump) for the recognition of popular songs from 1945 to 1995 was found at an SSA of about 17–19 years. To summarize, all these studies showed a high diversity of age peaks covering a wide age range (an observation which is supported by the systematic review by Munawar et al, 2018).…”
Section: Literaturementioning
confidence: 99%
“…Sporadic findings of a small reminiscence effect in PEK might therefore be driven by the autobiographical content of these public events when experienced firsthand. This would also explain findings of a reminiscence bump in studies that ask about favorite music or popular songs (e.g., Rathbone et al, 2017;Zimprich, 2020), for which personal significance and emotional arousal play a role. Identification with the music listened to in adolescence and early adulthood affects the self-narrative markedly (Holmes & Conway, 1999), which later facilitates recall of these experiences.…”
Section: Pek As Experience-based Knowledgementioning
confidence: 94%
“…Reminiscence bumps were also found for autobiographical memories elicited under more or less restrictive recall instructions, for example, for vivid or important autobiographical memories (e.g., Ece & Gülgöz, 2014;Fitzgerald, 1988;Glück & Bluck, 2007;Rubin & Schulkind, 1997a;Webster & Gould, 2007), or free (uncued) recall from different periods of participants' lives (e.g., Conway, Wang, Hanyu, & Haque, 2005;Demiray et al, 2009). Moreover, reminiscence bumps have been found for preferences in cultural life such as literature, film, or music (Holbrook & Schindler, 1989;Janssen et al, 2007;Larsen, 1996;Rathbone, O'Connor, & Moulin, 2017;Zimprich, 2018;.…”
Section: Theoretical Accounts Of the Reminiscence Bump Phenomenonmentioning
confidence: 97%